2003
DOI: 10.1108/09590550310469185
|View full text |Cite
|
Sign up to set email alerts
|

An empirical evaluation of US bank customer perceptions of the impact of technology on service delivery in the banking sector

Abstract: The instalment of customer friendly technology (such as menu driven automated teller machines, telephone and Internet banking services) as a means of delivering traditional banking services has become commonplace in recent years as a way of maintaining customer loyalty and increasing market share. Traditional brick and mortar banks are using technology to meet the competitive challenge posed by online banks, as well as a method of reducing the cost of providing services that were once delivered exclusively by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
138
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(141 citation statements)
references
References 31 publications
1
138
0
2
Order By: Relevance
“…Specific attributes of ATM banking were adopted from empirical researches; Al Hawari et al (2006), Athanassopoulos (2000), Davies et al (1996), Howcroft (1991), Joseph and Stone (2003), Moutinho and Brownlie (1989), Patricio et al (2003), and Yavas et al (2004). 25 ATM banking attributes in total were adopted from empirical studies and were categorized into the five service quality dimensions of tangibles, reliability, responsiveness, assurance and empathy (Parasuraman, et al, 1988).…”
Section: Research Modelmentioning
confidence: 99%
“…Specific attributes of ATM banking were adopted from empirical researches; Al Hawari et al (2006), Athanassopoulos (2000), Davies et al (1996), Howcroft (1991), Joseph and Stone (2003), Moutinho and Brownlie (1989), Patricio et al (2003), and Yavas et al (2004). 25 ATM banking attributes in total were adopted from empirical studies and were categorized into the five service quality dimensions of tangibles, reliability, responsiveness, assurance and empathy (Parasuraman, et al, 1988).…”
Section: Research Modelmentioning
confidence: 99%
“…Previous IPA research regarding banking customers' perceptions of bank service delivery technologies have focused on single-country studies including the United States (Joseph and Stone, 2003), Australia and the United Kingdom (Ennew et al, 1993). While the aforementioned studies have provided useful insights regarding customer perceptions within a single nation, these inquiries do not explicitly compare bank customer perceptions across two or more nations.…”
Section: Introductionmentioning
confidence: 99%
“…Customers may also differ as to the degree of importance they place upon various service quality evaluation criteria such as the speed and efficiency in consummating a service transaction, accuracy of the outcome of a transaction, feelings of autonomy and self-control during a transaction, widespread accessibility to a service, ease of understanding of how to use a service, amount of time spent waiting in a service delivery queue, feelings of personal comfort and safety, availability of employees to handle complaints, confidence in the bank, personalised greetings from technologies/employees and aesthetic surroundings (Joseph and Stone, 2003).…”
Section: Strategic Perceptions Of Banking Service Delivery Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the marketing literature has recognized the importance of developing and maintaining enduring relationships with customers of service businesses (Henning-Thurau et al, 2002) and as cited in So and Speece (2000), Perrien et al (1992) suggested that strong competitive pressure has forced financial institutions to revise their marketing strategies and to stress long-lasting relationships with customers. Indeed, Joseph and Stone (2003) indicated that the importance of service delivery and its impact on improving satisfaction and retention of customers cannot be overstated. Mobolaji (2009) studied banking development, human capital and economic growth in Sub-Saharan Africa (resource challenged environment) and posited that despite the myriads of hope, growth and performance of Africa has been very poor.…”
Section: Service Delivery In Developing Countries Context -Literaturementioning
confidence: 99%